Abstract Spatial Concept Priming Dynamically Influences Real-World Actions - Tower-Richardi, Sarah M.; Brunye, Tad T.; Gagnon, Stephanie A.; Mahoney, Caroline R.; Taylor, Holly A. (Frontiers in Psychology, 2012)
Experienced regularities in our perceptions and actions play important roles in grounding abstract concepts such as social status, time, and emotion. Might we similarly ground abstract spatial concepts in more experienced-based domains? The present experiment explores this possibility by implicitly priming abstract spatial terms (north, south, east, west) and then measuring participants’ hand movement trajectories while they respond to a body-referenced spatial target (up, down, left, right) in a verbal (Exp. 1) or spatial (Exp. 2) format. Results from two experiments demonstrate temporally-dynamic and prime-biased movement trajectories when the primes are incongruent with the targets (e.g., north – left, west – up). That is, priming abstract coordinate directions influences subsequent actions in response to concrete target directions. These findings provide the first evidence that abstract concepts of world-centered coordinate axes are implicitly understood in the context of concrete body-referenced axes; critically, this abstract-concrete relationship manifests in motor movements, and may have implications for spatial memory organization.